Model-based specification and testing applied to the Ground-Based Midcourse Defense (GMD) system an industry report. - Lakey, Peter B. (Software engineering notes.)
Cognitive Concepts LLC (CC) is a small business that specializes in software reliability engineering. In the past several years CC has become convinced that the best available practice for software reliability on complex systems is model-based specification and testing (MST). CC completed a small business innovative research project with the Missile Defense Agency in 2004 in which the goal was to demonstrate the feasibility and value of applying MST on some aspect of the National Missile Defense (NMD). This paper describes the results of that research effort.